A single test for the determination of parameters of the speed-time relationship for running - Broxterman, R. M.; Ade, C. J.; Poole, David C.; Harms, Craig A.; Barstow, Thomas J. (My University, 2013)
A validated expeditious method is needed to determine critical speed (CS) and the finite distance that can be covered above CS (D`). We tested the hypothesis that a single all-out 3-min running test would accurately determine CS and D`. Seven healthy subjects completed three constant-speed runs on a treadmill for the determination of CS and D`, as well as an all-out 3-min test on a track for the determination of end-test speed (ES) and the distance above end-test speed (DES). ES (13.4 ± 2.8 km•hˉ¹) was not significantly different from the speed-1/time model CS (13.3 ± 2.8 km•hˉ¹). While DES (141 ± 34 m) was not significantly different from D` (204 ± 103 m), it underestimated D` in 5 of 7 subjects. Thus, the speed-1/time model CS can be accurately determined using a single 3-min test, while caution should be used in relating DES to D`.
Keywords: All-out test; Critical speed; D`; Running